Virulence factors, antibiotic resistance genes and genetic relatedness of commensal Escherichia coli isolates from dogs and their owners. (March 2018) - Derakhshandeh, Abdollah; Eraghi, Vida; Boroojeni, Azar Motamedi; Niaki, Malihe Akbarzadeh; Zare, Sahar; Naziri, Zahra
Abstract: Escherichia coli ( E. coli ) is a normal flora of gastrointestinal tracts of humans and warm-blooded animals including dogs that has close vicinity with humans. Because the inter-species transmission of E. coli between pets and human beings, within a household, obtaining more information about the epidemiology, genetics, virulence factors, and antibiotic resistance of E. coli from dogs and their owners will help to control the inter-species transmission and treatment of E. coli infections. In this study we characterize and compare the antibiotic resistance and virulence profiles of fecal E. coli isolates from dogs and their owners. A total of 149 commensal E. coli isolates comprised 62 isolates from dogs, 56 isolates from their owners and 31 isolates from humans with no pet as control were collected. Extracted DNA was assessed for the presence of antibiotic resistance genes cml A (chloramphenicol), sul I (sulfamethoxazole), floR (florfenicol) and bla CTX-M1 (cefotaxime) and virulence genes ( papA, ompT, hlyD, traT, tsh and cnf1 ). To determine the extent of genetic relatedness of isolates, RAPD-PCR was performed. sulI and traT genes were the most dominant resistance profile and the most prevalent virulence gene in all groups, respectively, while hlyD had the lowest frequency among investigated virulence genes. Based on RAPD-PCR analysis clonal sharing between dogs and their owners were observed in 2/28 (7.1%) potential within-household clone-sharing pairs. Allowing dog to lick on owner's face, dog sex (female dogs), dog's sexual status (intact dogs) and times of disposing the feces (≥twice a day) were associated with a higher percentage of RAPD profile similarity (P < 0.05). The current study did not show an obvious evidence to prove considerable transmission of fecal E. coli from dogs to their owners. But in two households, there were relationship between isolates from dogs and their owners. Highlights: The most prevalent virulence gene among all isolates was tra T. The most prevalent resistance gene among all isolates was sul I. Clonal sharing was observed in 7.1% of dogs and their owners. Licking owner's face by dog has a potential role in inter-species bacterial sharing.